Jewish occupational attainment in the antebellum United States: Filling a gap in the literature - Barry R. Chiswick; RaeAnn H. Robinson (Global Labor Organization (GLO), 2025)
This paper is concerned with analyzing the occupational attainment of American Jewish men compared to other free men in the mid-19th century to help fill a gap in the literature on Jewish achievement. It does this by using the full count (100 percent) microdata file from the 1850 Census of Population, the first census to ask the occupation of free men. Independent lists of surnames are used to identify men with a higher probability of being Jewish. These men were more likely than others to be managers, salesmen, and craft workers, and were less likely to be farmers and laborers. The Jewish men have a higher occupational income score on average. In the multiple regression analysis, it is found that among Jewish and other free men occupational income scores increase with age (up to about age 43 for all men), literacy, being married, having fewer children, being native born, living in the South, and living in an urban area. Even after controlling for these variables that impact the occupational income score, Jews have a significantly higher score, which is the equivalent of about the size of the positive effect of being married. Similar patterns are found using the Duncan Socioeconomic Index. This higher occupational status is consistent with patterns found elsewhere for American Jews for the 18th century and throughout the 20th century.
Keywords: N31; J62; J15; 330; Jews; Occupational Status; Occupational Income Score; Duncan Socioeconomic Index; 1850 Census of Population